The manifestation of elements of argumentation and justification in criminal proceedings - V., Dzhafarov (Opción, 2019)
The article attempts to establish the purpose of the theory of argumentation for the criminal process and evidentiary law, at the same time to identify the boundaries of argumentation, validity and evidence. The leading approach to the study of this problem was applied comparatively right, as well as formally logical methods. As a result, only common sense is of real importance, since fictions, in any case, should be inferior to evaluating evidence according to internal conviction. In conclusion, it is the logical connections that underlie beliefs that form the basis of the arguments justifying the position itself